“Striving for Sufficient Milk to Have a Healthy Late Preterm Baby”: A Grounded Theory Study - Rungtawan Choijorhor; Kannika Kantaruksa; Jutamas Chotibang; Nonglak Chaloumsuk (Pacific Rim International Journal of Nursing Research, 2023)
Late preterm infants are at risk for more health problems than full-term infants. They require good nutrition for growth, and breast milk is the gold standard because it contains valuable nutrients. Such infants are increasing globally while exclusive breastfeeding rates are decreasing. This grounded theory study explored exclusive breastfeeding experiences among first-time mothers of late preterm infants. Seventeen mothers from Northern Thailand who had exclusively breastfed for the first six weeks were recruited by purposive sampling to provide the initial data, and they were interviewed in-depth for 30-60 minutes. Constant comparative analysis was used during data collection and analysis. Striving for sufficient milk to have a healthy baby emerged as the core category representing a process in which the mothers of late preterm infants had to exert great effort to produce sufficient milk for their infants. This process consisted of preparing for breastfeeding, overcoming the problem of insufficient milk supply, and managing to continue breastfeeding. In conclusion, perceived insufficient milk supply in first-time mothers was a threat to achieving exclusive breastfeeding of their late preterm infants. However, the desire to have a healthy baby results in mothers’ greater efforts to achieve a sufficient milk supply. Understanding the findings of this study by nurses, midwives, and other relevant health professionals about the breastfeeding perceptions of mothers of these infants can lead to better outcomes for mothers and babies. Supportive care regarding exclusive breastfeeding is needed for mothers throughout the sequence of antenatal, intrapartum, and postpartum care.